Yajurveda-svādhyāya tathā paśuyajña-samīkshā - Vidyālaṅkāra, Viśvanātha (Nārāyaṇa Siṃha, Pratāpa Siṃha ; prāpti-sthāna, Rāmalāla Kapūra Ṭrasṭa, 1979)
Study on the Yajurveda and Hindu sacrificial rites according to the Arya samaj sect of Hinduism.